Peningkatan Kesehatan Masyarakat Melalui Pemeberdayaan Wanita dalam Pemanfaatan Tanaman Obat Keluarga (TOGA) di Wilayah Kerja Puskesmas Rejosari Pekanbaru - Ary Oktora Sri Rahayu; Yesi Septina Wati; Meirita Herawati (Abdimas Universal, 2022)
Medicinal plants are plants that have medicinal properties and are used as drugs in healing and preventing disease, the use of natural materials is more acceptable to the human body. Knowledge about the use of medicinal plants is an important element in improving the ability of individuals and families to obtain a healthy life. It is important to continue educating the public regarding the benefits of TOGA. One of the functions of TOGA is as an effort to improve public health including preventive efforts (prevention), promotive efforts (improvement/maintaining health), and curative efforts (curing disease). The solution offered is to provide counseling in the form of education related to improving public health by using TOGA which is expected to provide input on TOGA. With the education carried out, it is able to empower the community in the use of family medicinal plants as an effort to increase body immunity in the midst of the covid-19 pandemic. PKM partners are 21 housewives. The method of implementing the activity is to begin by identifying the needs to be used, follow-up surveys and collection of tools and materials needed, then identify the mechanism for implementing community service activities as well as education and socialization. The resulting outputs are: 1) empowering the community in the use of family medicinal plants as an effort to increase body immunity, and 2) becoming a published scientific work.